2017
DOI: 10.7575/aiac.ijels.v.5n.4p.111
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Foreign Language Speaking Anxiety of Iranian English Language Learners

Abstract: Foreign language learning anxiety is one of the affective factors which influence language learning negatively. It has several sources and different types. The present study aimed at investigating the sources of foreign language speaking anxiety of Iranian EFL learners. To do so, 154 EFL learners participated in the study. They were required to fill out a foreign language anxiety questionnaire which was developed based on the Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, Horwitz, and Cope (1986)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 7 publications
5
61
2
1
Order By: Relevance
“…They also feel that their ability in speaking is inferior compared to their peers. This is distinctive from other studies which suggest that students feel the highest level of anxiety on fear of negative feedback, fear of failure, fear of making mistakes, and limited vocabulary (Alsowat, 2016;Sadighi & Dastpak, 2017).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…They also feel that their ability in speaking is inferior compared to their peers. This is distinctive from other studies which suggest that students feel the highest level of anxiety on fear of negative feedback, fear of failure, fear of making mistakes, and limited vocabulary (Alsowat, 2016;Sadighi & Dastpak, 2017).…”
Section: Discussioncontrasting
confidence: 95%
“…Some studies which delved into the level of students' language anxiety have shown that students have had moderate to high level of foreign language anxiety (Alrabai, 2014; Alsowat, 2016; Burden, 200 4; Suleimenova , 2012; Tianjian, 2010). Within this level of anxiety, students most likely feel anxious in terms of the worry of negative feedback, making mistakes, and vocabulary limitation (Sadighi & Dastpak, 2017). However , it is also found that the degree of language anxiety between male and female students is relatively similar (Ozuturk & Hursen, 2013; Shabani, 2012).…”
Section: Language Learning Anxiety In Efl Classroommentioning
confidence: 99%
“…Horwitz et al (1986), one of the first scholars dealing with the anxiety concept in language learning, investigated the speaking anxiety in relation to foreign language anxiety which is defined as "a distinct complex of self perceptions, feelings and behaviors related to classroom language learning arising from the uniqueness of the language learning process" (p.127). The related research studies showed that speaking anxiety causes stress, unintended performance and sometimes failure among language learners (Yahya, 2013;Sadighi & Dastpak, 2017). Similar findings have been reached by Liu (2007), it was found that the majority of the students felt somewhat anxious about oral English tests and that the more proficient students tended to be less anxious.…”
Section: Introductionmentioning
confidence: 61%
“…EFL learners are confronted with a lot of problems that negatively affect mastering English skills (Sadighi & Dastpak, 2017). Among those obstacles is the task of correct and fluent pronunciation.…”
Section: Resultsmentioning
confidence: 99%